2013
DOI: 10.1007/s10103-013-1430-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy (808 nm) on markers of muscle damage: a randomized double-blind placebo-controlled trial

Abstract: The aim of this randomized double-blind placebo-controlled study was to investigate the effect of low-level laser therapy (LLLT) on markers of muscle damage (creatine kinase (CK) and strength performance) in the biceps brachii. Twenty-two physically active men were randomized into two groups: placebo and laser. All volunteers were submitted to an exercise-induced muscle damage protocol for biceps brachii (biceps curl, 10 sets of 10 repetitions with load of 50% of one-repetition maximum test (1RM)). Active LLLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 30 publications
4
29
0
2
Order By: Relevance
“…The effects of low-level laser (light) therapy on muscle tissue when applied before or after intense exercise are mainly related to the prevention of exercise-induced damage, promotion of faster muscle recovery, and also producing increases in performance [10,30,11]. The use of LLLT to prevent muscle damage has been widely investigated in experimental models [15][16][17][18][19][20] and in clinical trials [21][22][23][24][25][26][27][28]. Experimental studies have used animal models to induce muscle damage, and clinical trials have used protocols of exercise in isokinetic dynamometers, fitness machines, or free weight lifting to induce muscle damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of low-level laser (light) therapy on muscle tissue when applied before or after intense exercise are mainly related to the prevention of exercise-induced damage, promotion of faster muscle recovery, and also producing increases in performance [10,30,11]. The use of LLLT to prevent muscle damage has been widely investigated in experimental models [15][16][17][18][19][20] and in clinical trials [21][22][23][24][25][26][27][28]. Experimental studies have used animal models to induce muscle damage, and clinical trials have used protocols of exercise in isokinetic dynamometers, fitness machines, or free weight lifting to induce muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported lower increases in CK activity measured in blood when LLLT was applied before intense exercises. Light doses (Joules, J) used in previous studies were between 1 and 6 J delivered per diode laser, totaling 4 J [21] or 60 J [22] delivered to the biceps brachii; 30 and 40 J [23] or 180 J [24] delivered to the quadriceps femoris muscles. When the light source was LED, these studies used a cluster of 69 LEDs and applied 0.3 or 0.9 J per LED, totaling 41.7 J per site of irradiation and a total dose of 41.7 J delivered on biceps brachii [25]; 83.4 J [26] or 125.1 J [27] or 208.5 J [28] delivered to quadriceps femoris muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas alterações na estrutura da célula promovem o processo de inflamação no tecido muscular, que é composto basicamente por três fases: degeneração, reparo e remodelamento. Essas fases apresentam características específicas e fundamentais para a adequada restauração da estrutura e função do tecido muscular lesado 14,15 . f) Regeneração de nervos periféricos -Nervos periféricos são alvo constante de lesões traumáticas que podem resultar em déficits motores com o decorrer do tempo que alteram suas propriedades mecânicas e neuroquímicas, bem como podem proporcionar complicações irreversíveis 3,12,[16][17][18] .…”
Section: Introductionunclassified
“…Phototherapy associated with resistance exercise protocols or muscular endurance has shown positive results, better than when performed in different groups, improving performance, endurance, and recovery from fatigue, proven by the various strength tests and the biomarker analyses such as lactate, creatine kinase, and C-reactive protein. [16][17][18][19][20][21][22][23][24][25] Leal-Junior et al 18 made a systematic review about LLLT/LEDT effects on performance among exercise, and at recovery markers after muscle fatigue. The study concludes that results more significant, and consistent, occurred with red or infrared wavelengths applied before exercise.…”
Section: Introductionmentioning
confidence: 99%